2011
DOI: 10.1002/cyto.b.20621
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation modulates the detection of regulatory T cell markers

Abstract: Background: Regulatory T cells (Tregs) modulate the host response in infectious diseases and are key mediators of peripheral tolerance. Cryopreservation of peripheral blood mononuclear cells (PBMCs) is commonly used in immunological field studies where access to complex laboratory tests is not feasible. Our objective is to assess the effects of cryopreservation on the flow cytometric detection of surface and intracellular markers of Tregs.Methods: Heparinized venous blood was obtained from 36 healthy individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 12 publications
3
45
3
1
Order By: Relevance
“…47 In the current study, both fresh and cryopreserved samples were used for phenotypic characterization of Tregs. As there is conflicting data about whether or not cryopreservation reduces the percentage of Tregs in samples, 48,49 we analyzed SPL samples both freshly after isolation as well as after at least 1 month of cryopreservation in liquid nitrogen. We found no difference in the percentage of Tregs, their activation status, or their chemokine expression pattern (supplemental Figure 1, available on the Blood Web site).…”
Section: Discussionmentioning
confidence: 99%
“…47 In the current study, both fresh and cryopreserved samples were used for phenotypic characterization of Tregs. As there is conflicting data about whether or not cryopreservation reduces the percentage of Tregs in samples, 48,49 we analyzed SPL samples both freshly after isolation as well as after at least 1 month of cryopreservation in liquid nitrogen. We found no difference in the percentage of Tregs, their activation status, or their chemokine expression pattern (supplemental Figure 1, available on the Blood Web site).…”
Section: Discussionmentioning
confidence: 99%
“…Clone of anti-FoxP3 was PCH101. , specifically in cells from HIV-infected individuals [31]. However, some authors have reported comparable values of T regs in frozen samples and fresh samples, suggesting that these variations could be related to differences between cryopreservation and thawing protocols.…”
Section: Cd25mentioning
confidence: 99%
“…On the one hand, the heterogeneity of patients' population has to be taken into account (level of viremia, type of progressors, treatments duration : : : ). On the other hand, analytical issues may have contributed to discordances: markers used for Tregs phenotyping, staining of whole blood or purified cells, sample conservation (i.e., cryopreserved or not) (9,10).…”
mentioning
confidence: 99%